Hubungan Asupan Protein Dan Zat Besi Dengan KadarHemoglobin Pada Pasien Gagal Ginjal Kronik Post HemodialisiDi Unit Hemodialisis Rsud Kabupaten Sukoharjo - Hasanah, Ika Purnama Fitria; , Ahmad Farudin, SKM, M.Si; , Elida Soviana, S.Gz, M.Gizi (2016)
Background. CRF is a clinical condition of progressive kidney damage and irreversible with diverse etiology. Hemodialysis is cataboloc process. In the hemodialysis process occurs excretion of amino acids through the dialysate and a decrease in protein synthesis. Severe anemia is also a complication that occurs in patients with CRF. Nutrient intakes play role in the formation of red blood cells. Disruption of the formation of red blood cells can be caused by low consumption of important nutrients like protein and other nutrients. Objective. This study purposed to determine the relationship between the intakes of protein and iron and hemoglobin level in post hemodialysis chronic renal failure patients at General Hospital of Sukaharjo. Research method. The type of research was observational with cross sectional design.Object retrieval technique used consecutive sampling. The number of research subjects were 31 subjects. Intakes of protein and iron data were obtained using semi-quantitative food frequency quistionaire, while the hemoglobin level data were obtained trough cyanmethglobin semi-quantitative method test. Correlation test used spearman rank and the person product moment tests. Result. Most respondents had high protein intake (51,6%). Most responden had low intake of iron (41,9%) and high intake of iron (38,7%). There was 74,2% of respondents who had abnormal level of hemoglobin. The relationship between protein intake and hemoglobin level showed p: 0,292 while the corelation between iron intake and hemoglobin level showed p: 0,272. Conclusion. There was no relationship between intakes of protein and iron levels and hemoglobin level in post hemodialysis CRFpatients at general hospital of sukoharjo. Key word : chronic renal failure, hemodialysis, protein intake, ironi ntake, hemoglobin. Library : 69 : 2000-2012